Advances in separation by ionic strength: Association of chromatography and ionic liquids or deep eutectic solvents for the purification of microalgae-based products - Veríssimo, Nathalia Vieira Porphirio [UNESP]; Mussagy, Cassamo Usemane; de Lima, Júlio Gabriel Oliveira [UNESP]; Santos-Ebinuma, Valéria de Carvalho [UNESP] (Elsevier, 2024)
Microalgae can generate several biomolecules for application in the food, pharmaceutical, and materials industries. However, it is challenging to implement sustainable and economically feasible marine biotechnological processes due to the complexity of recovering and purifying bioactive biomolecules from microalgae biomass. In this sense, ionic liquids (ILs) and deep eutectic solvents (DESs) can help to reduce environmental impacts and costs of biomolecule recovery from microalgae biomass by integrating different phases of their downstream processing (e.g., cell lysis, extraction, and purification) due to diversity, tunable nature, low vapor pressure, high thermal stability, and low toxicity of many ILs and DESs classes. However, researchers must select ILs and DESs compatible with the equipment and methods used to produce these microalgae-derived products. With this in mind, this chapter will reveal the latest advances in the recovery of bioproducts from microalgae biomass with ILs and DESs and the possibility of applying these ionic compounds to enhance the efficiency and purification potential of different types of chromatography.
Keywords: Chromatography matrices; Deep eutectic solvents; HPLC; Ionic liquids; Microalgae biomass; Mobile phase; Purification of biomolecules; Stationary phase